Towards an Understanding of Conservation-Based Costs, Benefits, and Attitudes of Local People Living Adjacent to Save Valley Conservancy, Zimbabwe - Given Matseketsa; Gladman Chibememe; Never Muboko; Edson Gandiwa; Kudakwashe Takarinda (Scientifica)
Communities juxtaposed to protected areas (PAs) often disproportionally accrue the costs of conservation, but they can also receive benefits from the existence of a PA. The extent to which local communities benefit or incur costs as a result of residing next to PAs is of interest to conservationists and policy-makers. This study sought to understand the costs, benefits, and attitudes of local people living adjacent to Save Valley Conservancy (SVC), Zimbabwe. The purpose was to determine whether benefit and loss accrual has a bearing on the levels of illicit wildlife-based activities experienced in the SVC. Data were collected through a household questionnaire survey and key informant interviews from April to July 2014. A three-stage sampling was adopted: firstly, purposive sampling was employed to select wards adjacent to the SVC; secondly, random sampling was used to select villages within the selected wards; and thirdly, systematic sampling was used to select 71 household questionnaire respondents. Snowball sampling was used to select 9 key informants. The study results show that the majority of locals living close to SVC are not deriving discernable benefits and the costs of conservation are escalating influencing negative attitudes towards wildlife conservation, thus causing them to view wildlife as a nuisance. Overall, our results indicate that conservation losses and benefit accrual by local communities influence their attitudes toward SVC and conservation in general. We conclude that costs incurred outweighed the benefits accrued, a situation that triggers a more negative form of reciprocity towards SVC and wildlife conservation. It is recommended that a more socially and economically inclusive management approach based on a stakeholder-driven access and benefit sharing (ABS) framework be instituted to promote a more positive form of reciprocity towards SVC and nature conservation.